Ambient Air Quality Assessment in the Limestone Mining Area of Ponjong District, Gunung Kidul, Indonesia - Tasidjawa, Gabriela Elisabeth; Ernawati, Rika; Cahyadi, Tedy Agung; Nursanto, Edy; Haq, Shofa Rijalul; Setiyawa, Meindra (Journal of Earth and Marine Technology (JEMT), 2024)
Limestone, a non-metallic industrial mineral, is abundantly found across Indonesia. The extraction process involves overburden removal, limestone breaking using rock breakers, loading onto dump trucks with excavators, stockpiling, and subsequent processing. These activities can negatively impact the environment, particularly air quality. To evaluate the ambient air quality in the mining area, measurements were taken focusing on hazardous substances such as SO2, CO, NO2, O3, and Total Suspended Particles (TSP). This study aims to assess the ambient air quality within the limestone mining area. Results indicate that the ambient air quality in the mining area is relatively good, with no parameters exceeding established quality standards. Specifically, SO2 levels were 9.39 µg/m³, NO2 levels were 4.19 µg/m³, CO levels were 69.74 µg/m³, O3 levels were 24.90 µg/m³, and TSP levels were 133.26 µg/m³. For a more comprehensive assessment, it is recommended to conduct extended monitoring of these parameters to ensure the long-term air quality status for both the environment and the mine workers